(untitled) (El Hilo de la Fabula, 2010)
This study sets a number of relationships between the foundational texts of the English literature and The waste land by T. S. Eliot since a recurrent theme in this tradition: “the journey by water”. By the means of a comparative lecture, this analysis will allow us to discern common aspects in the texts: the nostalgia and the desire which this journey originates and, particularly, the transformation of one in another.